2007
DOI: 10.1007/s00442-007-0683-5
|View full text |Cite
|
Sign up to set email alerts
|

Climate change affects timing and size of populations of an invasive cyanobacterium in temperate regions

Abstract: Cylindrospermopsis raciborskii, an invasive freshwater cyanobacterium, originated from the tropics but has spread to temperate zones over the last few decades. Its northernmost populations in Europe occur in North German lakes. How such dramatic changes in its biogeography are possible and how its population dynamics in the newly invaded habitats are regulated are still unexplained. We therefore conducted a long-term (1993-2005) study of two German lakes to elucidate the mechanisms behind C. raciborskii popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
155
0
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(172 citation statements)
references
References 53 publications
13
155
0
4
Order By: Relevance
“…Nitrogen fixation is a process known to require considerable energy expenditure and species from the order Nostocales require high degrees of luminosity in order to maintain it (MacCausland et al, 2005;Wiedner et al, 2007). According to Padisák (1997), the production of heterocysts occurs when there is a deficiency of nitrogen in the environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nitrogen fixation is a process known to require considerable energy expenditure and species from the order Nostocales require high degrees of luminosity in order to maintain it (MacCausland et al, 2005;Wiedner et al, 2007). According to Padisák (1997), the production of heterocysts occurs when there is a deficiency of nitrogen in the environment.…”
Section: Discussionmentioning
confidence: 99%
“…In a study on populations of C. raciborskii in two lakes in Germany, Wiedner et al (2007) found that growth initiated under light intensity ranging from 90 to 130 µmol.photons.m -2 .s -1 and at a temperature between 15 and 17 °C. The authors concluded that light intensity is the most important factor in the regulation of population dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…A well-studied aquatic example is the northward range expansion of the invasive cyanobacterium Cylindrospermopsis raciborskii (Wiedner et al 2007). Biogeographic studies within the AQUASHIFT consortium were focussed on dragonflies, snails, and ciliates.…”
Section: Range Shiftsmentioning
confidence: 99%
“…Temperature has been considered the major limiting factor for growth of C. raciborskii (Pa´disak, 1997;Wiedner et al, 2007), with its optimal growth rate in laboratory experiments being at 25-35 C (Saker & Griffiths, 2000;Briand et al, 2004;Castro et al, 2004;Chonudomkul et al, 2004). Furthermore, its akinete germination is temperature dependent, and germination occurs primarily from 22-23.5 C (Pa´disak, 1997).…”
Section: Introductionmentioning
confidence: 99%